Substrate laser processing method, application and laser enhanced energy conversion device
Through laser treatment of substrates, the existing catalyst synthesis process is solved, and the efficient synthesis and surface modification of catalyst and electrode materials are achieved, which significantly improves the energy conversion efficiency and stability, and meets the requirements of green chemistry and sustainable development.
Patent Information
- Application Number
- CN202411891129.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
AI Technical Summary
The existing catalyst synthesis process is complex, with low yield and poor uniformity, resulting in insufficient mechanical stability of the electrode and membrane electrode, inappropriate surface properties, and problems such as reactant conduction and desorption of the products.
By using the method of laser treatment of substrates, the chemical stability or mechanical stability of energy conversion materials and devices are improved by introducing laser-assisted synthesis and coating catalysts, surface-modified electrodes and membrane electrodes.
It significantly improves the activity of the catalyst and the density of surface reaction sites, improves energy conversion efficiency and stability, simplifies the preparation process, reduces costs, and reduces the use and emission of harmful chemicals.
Smart Images

Figure CN119681416A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalytic materials, and in particular to a method for laser processing a substrate, an application thereof, and a laser enhanced energy conversion device. Background Art
[0002] As the global demand for clean energy continues to grow, the importance of energy conversion and storage technologies has become increasingly prominent. As key means to promote the clean use of energy, technologies such as water electrolysis to produce hydrogen, fuel cells, and lithium batteries play an irreplaceable role in achieving carbon emission reduction and even the dual carbon goals. The core of these energy conversion and storage technologies lies in the electrochemical process, and efficient electrode materials and catalysts are important factors in improving the performance of these technologies.
[0003] In current energy conversion technologies, such as the use of nickel-based electrodes in alkaline water electrolysis and membrane electrode structures composed of platinum-based catalysts in fuel cells, electrodes or catalysts are used to accelerate charge transfer and electrochemical reaction rates. However, the existing catalyst synthesis process is complex, the yield is low, and the uniformity is poor, which leads to problems such as insufficient mechanical stability of electrodes and membrane electrodes, unsuitable surface properties for contact, and conduction of reactants and desorption of products. In addition, traditional methods make it difficult to accurately control the composition and structure of catalysts, thereby limiting the improvement of their catalytic activity and selectivity. Therefore, it is urgent to develop new synthesis processes and technologies to improve the preparation quality of catalysts and the performance of electrodes / membrane electrodes.
[0004] Traditional catalyst synthesis methods usually involve solid-phase reactions or wet chemical methods under high temperature and high pressure conditions, such as precipitation method, sol-gel method, etc. Although these methods can produce catalysts with certain effects, they are often accompanied by complex operating steps, long reaction time, low yield and difficult to control product morphology. In addition, in the post-synthesis post-processing process, steps such as washing, drying, and roasting also increase the cost and risk of environmental pollution. For some special nano-scale catalysts, due to the small particle size and easy agglomeration, dispersibility and stability become a major challenge.
[0005] In order to improve the surface properties of electrode materials, researchers have tried a variety of physical and chemical surface modification techniques, such as ion implantation, plasma treatment, chemical vapor deposition (CVD), atomic layer deposition (ALD), etc. Although these technologies can change the chemical composition or microstructure of the material surface to a certain extent, they generally have defects such as limited application range, expensive equipment, and complex processes, and it is difficult to achieve high-precision and large-area uniform treatment at the same time. Especially when facing flexible or three-dimensional complex-shaped electrodes, traditional surface modification techniques seem to be unable to cope with the situation.
[0006] In recent years, laser technology has shown great application potential in the field of materials science due to its unique spatiotemporal resolution, non-contact processing characteristics and highly controllable energy input methods. In particular, the development of short-pulse or ultrashort-pulse lasers has made fine processing at the micro-nano scale possible. Lasers can not only be used for rapid heating, melting, evaporation and other processes on the surface of materials, but can also induce electron transitions to accelerate chemical reactions and even generate photogenerated electrons to participate in reduction reactions. These characteristics make lasers an ideal tool for developing new catalyst synthesis processes and electrode surface modification methods.
[0007] In summary, there is an urgent need for a catalyst synthesis process and electrode surface modification technology that combine laser technology to meet the requirements of high-efficiency, low-cost, and environmentally friendly energy conversion devices. Summary of the invention
[0008] In view of the problems existing in the prior art, the present invention provides a method for laser processing a substrate, an application and a laser-enhanced energy conversion device, aiming to overcome the above-mentioned problems in the prior art, provide a more efficient and more accurate catalyst synthesis and electrode surface modification scheme, and thus promote technological innovation and development in related fields. The present invention greatly improves the chemical stability or mechanical stability of energy conversion materials and devices by introducing laser-assisted synthesis and coating of catalysts, surface modification of electrodes and membrane electrodes, and doping or forming heterogeneous structures on the electrode surface, laying a solid foundation for realizing a cleaner and more efficient energy system.
[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0010] A first aspect of the present invention provides a method for laser processing a substrate, comprising the following steps:
[0011] (1) placing the substrate in a container and adding a solution into the container, wherein the solution thickness is 0.1 mm to 10 cm;
[0012] (2) Using laser to locally supply energy to the substrate, so that the laser reacts with the solute in the solution, causing a physical or chemical reaction on the surface of the substrate, thereby completing the processing of the substrate.
[0013] Furthermore, the substrate is an electrode or a membrane electrode.
[0014] Furthermore, the substrate is any one of titanium felt, titanium plate, nickel felt, nickel plate, nickel foam, nickel mesh stainless steel, copper mesh, carbon paper, and ion exchange membrane.
[0015] Furthermore, the solution is any one of a metal salt solution, an inorganic acid solution, a non-metallic anion solution, a colloid, a catalyst precursor solution, a catalyst solution, and a catalyst slurry.
[0016] Furthermore, the metal salt is any one of iridium salt, ruthenium salt, nickel salt, platinum salt, iron salt, cobalt salt, sodium salt and potassium salt.
[0017] Furthermore, the inorganic acid is any one of nitric acid, sulfuric acid, hydrochloric acid, perchloric acid, sulfurous acid, and persulfuric acid.
[0018] Furthermore, the non-metallic anion is any one of a phosphate ion, a sulfate ion, and a halogen ion.
[0019] Furthermore, the colloid is a transition metal hydroxide dispersed in a liquid medium, and the transition metal hydroxide is any one of iron hydroxide, nickel hydroxide, and cobalt hydroxide.
[0020] Furthermore, the catalyst precursor is any one of soluble salts of iridium, ruthenium, platinum, iron, cobalt and nickel.
[0021] Furthermore, the catalyst is any one of a water electrolysis catalyst, a dye cell catalyst and a carbon dioxide electroreduction catalyst.
[0022] Furthermore, the laser is infrared light, visible light or ultraviolet light.
[0023] Furthermore, the wavelength of the laser is 100-2000nm.
[0024] Furthermore, the energy range of the laser is 1 mW to 100 W, preferably 5-10 W.
[0025] Furthermore, the laser treatment time is 1-20 min, preferably 2-10 min.
[0026] Furthermore, the spot diameter of the laser treatment is 0.001-10 mm, preferably 0.05-0.5 mm.
[0027] Furthermore, the laser moving speed is 1-200 cm / s, preferably 10-100 cm / s.
[0028] The second aspect of the present invention provides an application of the laser processing method for substrates in the synthesis and coating of catalysts, wherein the solution is a catalyst precursor solution, a catalyst solution or a catalyst slurry, and a laser is used to locally supply energy to the substrate. The solution receives the energy and evaporates, leaving a solute on the surface of the substrate. When the solute is a catalyst, the catalyst is coated on the surface of the substrate; when the solute is a catalyst precursor, the precursor is precipitated on the surface of the substrate, and the precursor is decomposed into a catalyst under the action of the laser, thereby realizing the synthesis of the catalyst on the surface of the substrate.
[0029] The third aspect of the present invention provides an application of the method for laser processing a substrate in the surface modification of an electrode or a membrane electrode, wherein the substrate is an electrode or a membrane electrode, and a laser is used to locally supply energy to the substrate. The solute in the solution undergoes a chemical reaction under the action of the laser and the product formed remains on the surface of the substrate, thereby achieving surface modification of the electrode or membrane electrode.
[0030] The fourth aspect of the present invention provides an application of the method of laser processing a substrate in doping or forming a heterostructure on the surface of a substrate, wherein a laser is used to locally supply energy to the substrate, electrons on the surface of the substrate are transferred to a solution, solutes in the solution receive the electrons to undergo a chemical reaction, and are doped into the substrate or form a heterostructure on the surface.
[0031] A fifth aspect of the present invention provides a material obtained by using the method of laser processing a substrate.
[0032] Furthermore, the material is one of an electrode or membrane electrode having a catalyst on its surface, an electrode or membrane electrode after surface modification, and an electrode or membrane electrode having a heterogeneous structure on its surface.
[0033] A sixth aspect of the present invention provides a laser enhanced energy conversion device further prepared using the material obtained by the method for laser processing a substrate.
[0034] Laser-enhanced energy conversion devices are highly efficient energy conversion devices that are prepared by finely processing materials or surface functionalization modification through laser processing technology. The device makes full use of the high energy density, precise control and local processing capabilities of the laser to achieve micro-nanostructure optimization of the substrate material and precise deposition of the catalyst, thereby improving the energy conversion efficiency and stability of the device. During the laser processing process, local energy supply can induce physical or chemical reactions between the solution and the substrate surface, such as catalyst deposition, doping formation, surface modification or heterogeneous structure generation.
[0035] The conversion device prepared by the present invention improves the activity of the catalyst and the density of surface reaction sites through laser treatment, thereby significantly improving the energy conversion efficiency. In addition, the present invention can achieve customized design of the surface microstructure and chemical properties of the material through the regulation of laser parameters (wavelength, power, spot diameter, scanning speed, etc.), so that the prepared conversion device has the characteristics of precision and controllability.
[0036] The seventh aspect of the present invention provides the application of the material obtained by the method of laser processing a substrate or a laser enhanced energy conversion device prepared by the material in the water electrolysis and chlor-alkali industries and in the electrolysis hydrogen production and fuel cell industries.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] The present invention realizes efficient synthesis and surface modification of catalysts and electrode materials by adopting a method of laser processing substrates, and significantly improves the performance of the materials. Utilizing the high energy and precise control characteristics of lasers, the present method can accurately synthesize and coat catalysts on the surface of substrates, and at the same time realize modification of the surface of electrodes or membrane electrodes, thereby improving the chemical stability or mechanical stability of materials and devices. Compared with traditional methods, the present invention not only simplifies the preparation process and reduces costs, but also enhances the electrochemical activity and durability of materials. In addition, the application of laser processing technology makes the preparation of catalysts and electrode materials more environmentally friendly, reduces the use and emission of harmful chemicals, and meets the requirements of green chemistry and sustainable development. In general, the present invention provides an efficient, low-cost, and environmentally friendly technical solution for the development of clean energy technologies such as water electrolysis to produce hydrogen and fuel cells, and has important industrial application value and broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a microscope photograph of the iridium surface-modified nickel foam electrode prepared in Example 5. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It is worth noting that the methods used in the present invention are conventional methods unless otherwise specified; the raw materials and devices used are conventional commercially available products unless otherwise specified, and their sources are not specifically limited.
[0041] Example 1
[0042] This embodiment provides a method for laser processing a substrate for preparing a fuel cell catalyst layer, comprising the following steps:
[0043] (1) Using 20 μm thick Nafion (perfluorosulfonic acid resin) as a substrate, polishing it to a rough surface and placing it in a glass container, mixing 10 mg of platinum carbon catalyst with 0.1 ml of 5% Nafion ethanol solution to prepare a slurry as a solution, adding it into the container, keeping the solution height at 0.2 cm;
[0044] (2) Set the laser parameters to wavelength 248nm, 0.1mm spot, 5W power, 10cm / s moving speed, and 5*5cm 2 The substrate area was laser treated for 2 min, and the loading was about 0.2 mg / cm 2The cathode catalyst layer of the fuel cell with platinum loading was then flipped and treated with the same laser parameters for 5 minutes to obtain 0.5 mg / cm 2 Platinum-loaded fuel cell anode catalyst layer.
[0045] The catalyst layer is at 10 mA / cm 2 The dissociation amount after 100h oxygen evolution reaction under constant current conditions is 0.06ug. The catalyst dissociation amount of the platinum carbon catalyst prepared by chemical reduction under the same temperature environment is 0.21ug. The chemical stability and durability of the catalyst layer of the present invention have significant advantages.
[0046] Example 2
[0047] This embodiment provides a method for laser processing a substrate, which is used to prepare an anode catalyst layer for electrolyzing water, and includes the following steps:
[0048] (1) Using 150 μm thick Nafion as the substrate, polishing it to a rough surface and placing it in a PFTE container, adding 0.2 mol / L iridium trichloride solution, and maintaining the solution height at 0.4 cm;
[0049] (2) Set the laser parameters to wavelength 248nm, 0.05mm spot, 10W power, 50cm / s moving speed, for 5*5cm 2 The substrate area was laser treated for 10 min to obtain an iridium loading of 1.0 mg / cm 2 Anode catalyst layer for water electrolysis.
[0050] The catalyst layer is at 10 mA / cm 2 The dissociation amount of the oxygen evolution reaction after 100h under constant current conditions is 0.08ug. The catalyst dissociation amount of the iridium-based catalyst prepared by chemical reduction under the same temperature environment is 0.25ug. The chemical stability and durability of the catalyst layer of the present invention have significant advantages.
[0051] Example 3
[0052] This embodiment provides a method for laser processing a substrate for preparing a nickel-iron hydroxide catalyst, comprising the following steps:
[0053] (1) A 200-mesh nickel mesh was placed as a substrate in a glass container, and 1 mol / L ferric chloride solution was added, with the solution height maintained at 2 cm;
[0054] (2) Set the laser parameters to wavelength 633nm, 0.2mm spot, 10W power, and 20cm / s moving speed for 5*5cm 2 The substrate area was laser treated for 8 minutes to obtain a two-dimensional layered nickel-iron hydroxide with a surface thickness of about 20 microns.
[0055] The nickel iron hydroxide catalyst was 2 The attenuation rate of the oxygen evolution reaction tested under constant current conditions is about 0.11 mV / h, and the attenuation rate of the nickel-iron hydroxide obtained by natural corrosion without laser treatment is about 0.34 mV / h. The electrocatalytic durability of the catalyst of the present invention is significantly improved.
[0056] Example 4
[0057] This embodiment provides a method for laser processing a substrate for preparing a nickel sulfide catalyst, comprising the following steps:
[0058] (1) A 200 μm nickel felt was placed as a substrate in a glass container, and 2 mol / L sodium thiosulfate was added as a solution, and the solution height was maintained at 2 cm;
[0059] (2) Set the laser parameters to wavelength 633nm, 0.2mm spot, 10W power, and 20cm / s moving speed for 5*5cm 2 The substrate area was laser treated for 8 minutes to obtain nickel sulfide with a surface thickness of about 20 microns.
[0060] The nickel-sulfur catalyst is 10 mA / cm 2 The attenuation rate of the hydrogen evolution reaction tested under constant current conditions is about 0.03 mV / h, and the attenuation rate of the nickel-sulfur catalyst obtained by natural corrosion without laser treatment is about 0.11 mV / h. The electrocatalytic durability of the catalyst of the present invention is significantly improved.
[0061] Example 5
[0062] This embodiment provides a method for laser processing a substrate, which is used to modify the surface of a foam nickel electrode, and includes the following steps:
[0063] (1) Place 100 μm nickel foam as a substrate in a glass container, add 0.1 mol / L H2IrCl6 as a solution, and keep the solution height at 1 cm;
[0064] (2) Set the laser parameters to wavelength 1064nm, 0.05mm spot, 10W power, 50cm / s moving speed, for 1*2cm 2 The substrate area was laser treated for 5 min to obtain a nickel foam electrode with iridium surface modification, as shown in the microscope photo. Figure 1 shown.
[0065] After 30 minutes of 100W power ultrasound (5L volume) for the nickel foam electrode after laser surface modification, the surface powder loss rate is about 9%, while the surface powder loss rate of the nickel foam electrode without laser modification is about 49% under the same ultrasonic conditions. The mechanical stability of the surface modified electrode prepared by the present invention is significantly improved.
[0066] Example 6
[0067] This embodiment provides a method for laser processing a substrate, which is used to form a heterogeneous structure on the surface of the substrate, including the following steps:
[0068] (1) A titanium felt with a thickness of 150 μm was placed as a substrate in a PTFE container, and 0.05 mol / L H2PtCl6 was added as a solution, and the solution height was maintained at 0.8 cm;
[0069] (2) The laser parameters were set to a wavelength of 1064 nm, a spot size of 0.2 mm, a power of 10 W, and a moving speed of 20 cm / s. The substrate area of 5*5 cm2 was laser treated for 10 min to obtain a titanium felt with a surface Pt coating of 50 nm.
[0070] After 30 minutes of 100W power ultrasound (5L volume), the surface powder loss rate of the laser-treated titanium electrode was about 5%, while the surface powder loss rate of the titanium electrode not treated with laser was about 27% under the same ultrasonic conditions. The mechanical stability of the electrode with a heterogeneous structure on the surface prepared by the present invention is significantly improved.
[0071] Example 7
[0072] This embodiment provides a method for laser processing a substrate, which is used to modify the surface of a membrane electrode, and includes the following steps:
[0073] (1) The width is 30 cm and the cathode loading is 0.4 mg / cm 2 , anode loading 1mg / cm 2 The membrane electrode was used as a substrate in a roll-to-roll manner, and hydrogen peroxide was used as a solution, and the solution height was maintained at 0.5 cm;
[0074] (2) The laser parameters were set to a wavelength of 1064 nm, a spot size of 0.5 mm, a power of 5 W, and a moving speed of 100 cm / s, and the substrate was continuously laser treated to obtain a surface modified membrane electrode with a surface water contact angle of 50°.
[0075] The tensile strength of the membrane electrode after laser surface modification is about 42 MPa / m, and the tensile strength of the membrane electrode without laser modification is about 30 MPa / m. The mechanical stability of the surface modified membrane electrode prepared by the present invention is significantly improved.
[0076] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for laser processing a substrate, comprising the following steps: (1) placing the substrate in a container and adding a solution into the container, wherein the solution thickness is 0.1 mm to 10 cm; (2) using laser to locally supply energy to the substrate, so that the laser reacts with the solute in the solution, causing a physical or chemical reaction on the surface of the substrate, thereby completing the treatment of the substrate; The substrate is an electrode or a membrane electrode, and the solution is any one of a metal salt solution, an inorganic acid solution, a non-metallic anion solution, a colloid, a catalyst precursor solution, a catalyst solution, and a catalyst slurry.
2. The method for laser processing a substrate according to claim 1, characterized in that: The substrate is any one of titanium felt, titanium plate, nickel felt, nickel plate, foamed nickel, nickel mesh stainless steel, copper mesh, carbon paper, and ion exchange membrane.
3. The method for laser processing a substrate according to claim 1, characterized in that: The metal salt is any one of iridium salt, ruthenium salt, nickel salt, platinum salt, iron salt, cobalt salt, sodium salt and potassium salt.
4. The method for laser processing a substrate according to claim 1, characterized in that: The inorganic acid is any one of nitric acid, sulfuric acid, hydrochloric acid, perchloric acid, sulfurous acid, and persulfuric acid.
5. The method for laser processing a substrate according to claim 1, characterized in that: The non-metallic anion is any one of phosphate ion, sulfate ion and halogen ion.
6. The method for laser processing a substrate according to claim 1, characterized in that: The colloid is a transition metal hydroxide dispersed in a liquid medium, and the transition metal hydroxide is any one of iron hydroxide, nickel hydroxide, and cobalt hydroxide.
7. The method for laser processing a substrate according to claim 1, characterized in that: The catalyst precursor is any one of soluble salts of iridium, ruthenium, platinum, iron, cobalt and nickel.
8. The method for laser processing a substrate according to claim 1, characterized in that: The catalyst is any one of a water electrolysis catalyst, a dye cell catalyst and a carbon dioxide electroreduction catalyst.
9. The method for laser processing a substrate according to claim 1, characterized in that: The laser is infrared light, visible light or ultraviolet light.
10. The method for laser processing a substrate according to claim 1, characterized in that: The wavelength of the laser is 100-2000nm.
11. The method for laser processing a substrate according to claim 1, characterized in that: The energy range of the laser is 1 mW-100 W, preferably 5-10 W.
12. The method for laser processing a substrate according to claim 1, characterized in that: The laser treatment time is 1-20 min, preferably 2-10 min.
13. The method for laser processing a substrate according to claim 1, characterized in that: The spot diameter of the laser treatment is 0.001-10 mm, preferably 0.05-0.5 mm.
14. The method for laser processing a substrate according to claim 1, characterized in that: The laser moving speed is 1-200 cm / s, preferably 10-100 cm / s.
15. Application of the method for laser processing of substrates according to any one of claims 1 to 14 in the synthesis and coating of catalysts, wherein the solution is a catalyst precursor solution, a catalyst solution or a catalyst slurry, and a laser is used to locally supply energy to the substrate, and the solution receives the energy and evaporates, leaving a solute on the surface of the substrate. When the solute is a catalyst, the coating of the catalyst on the surface of the substrate is achieved; when the solute is a catalyst precursor, the precursor is precipitated on the surface of the substrate, and the precursor is decomposed into a catalyst under the action of the laser, thereby achieving the synthesis of the catalyst on the surface of the substrate.
16. Application of the method for laser processing of substrates as described in any one of claims 1 to 14 in surface modification of electrodes or membrane electrodes, wherein the substrate is an electrode or a membrane electrode, and laser is used to locally supply energy to the substrate, solutes in a solution react chemically under the action of the laser to form products that remain on the surface of the substrate, thereby achieving surface modification of the electrode or membrane electrode.
17. Application of the method for laser processing of substrates according to any one of claims 1 to 14 in doping or forming a heterostructure on the surface of a substrate, wherein laser is used to locally supply energy to the substrate, electrons on the substrate surface are transferred to a solution, solutes in the solution receive the electrons to undergo a chemical reaction, and are doped into the substrate or form a heterostructure on the surface.
18. A material obtained by the method for laser processing a substrate according to any one of claims 1 to 14.
19. The material according to claim 18, characterized in that The material is one of an electrode or membrane electrode with a catalyst on the surface, an electrode or membrane electrode after surface modification, and an electrode or membrane electrode with a heterogeneous structure on the surface.
20. A laser enhanced energy conversion device, characterized in that: Comprising the material of claim 18 or 19.
21. Application of the material according to claim 18 or 19 or the laser enhanced energy conversion device according to claim 20 in water electrolysis and chlor-alkali industries and in hydrogen electrolysis and fuel cell industries.